2015
DOI: 10.7589/2013-06-139
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity Breeds Contempt: Combining Proximity Loggers and GPS Reveals Female White-Tailed Deer (Odocoileus Virginianus) Avoiding Close Contact With Neighbors

Abstract: ABSTRACT:Social interactions can influence infectious disease dynamics, particularly for directly transmitted pathogens. Therefore, reliable information on contact frequency within and among groups can better inform disease modeling and management. We compared three methods of assessing contact patterns: (1) space-use overlap (volume of interaction [VI]), (2) direct contact rates measured by simultaneous global positioning system (GPS) locations (,10 m apart), and (3) direct contact rates measured by proximity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
(51 reference statements)
1
22
0
Order By: Relevance
“…In suburban landscapes, space use is condensed because of the highly fragmented distribution of cover and food resources (Grund et al , Walter et al , Potopov et al ). Our findings are in agreement with recent studies that report that, although deer from the same social group do overlap and move together, deer from different social groups also frequently share space and may even come into contact with members of other groups (Magle et al , Schauber et al , Tosa et al ).…”
Section: Discussionsupporting
confidence: 94%
“…In suburban landscapes, space use is condensed because of the highly fragmented distribution of cover and food resources (Grund et al , Walter et al , Potopov et al ). Our findings are in agreement with recent studies that report that, although deer from the same social group do overlap and move together, deer from different social groups also frequently share space and may even come into contact with members of other groups (Magle et al , Schauber et al , Tosa et al ).…”
Section: Discussionsupporting
confidence: 94%
“…Some genetic studies of whiteā€tailed deer corroborated the expected difference (Grear et al , Cullingham et al ), but others reported somewhat unexpected results including relatively low relatedness among coā€occurring females (Comer et al ) and lower spatial genetic autocorrelation among female yearlings compared to male yearlings (Kelly et al ). A host of factors have been suggested for reasons why fineā€scale genetic structure among females may be less evident than expected including greater hunting pressure, which is thought to increase dispersal rates and alter social group formation (Comer et al ; Tosa et al , ); a high degree of spatial overlap among social groups (Comer et al ); and lower variability in male breeding success, which dilutes the pattern of female relatedness in social groups (Blanchong et al ). In areas where forested patches are highly fragmented, such as northern Missouri, female dispersal rates may be more equal to males (Nixon et al ) and recent field observations corroborate this trend (B. J. Keller, Missouri Department of Conservation, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding study-specific trade-offs, the spatial information associated with contacts can remarkably increase the robustness of inference on animal encounters [36], enhancing a process-based interpretation of these observations [37]. This may prompt a completely new set of questions in behavioural ecology (e.g.…”
Section: Trialmentioning
confidence: 99%